On a Class of Meromorphic Functions Related to Cho-Kwon-Srivastava Operator. (6th May 2012) - Ghanim, F.; Darus, M.
Abstract : We introduce new classes, Σ n, λ *, μ, k ( α, β, ρ ) and Σ n, λ μ, k ( α, β, ρ ), of meromorphic functions defined by means of the Hadamard product of Cho-Kwon-Srivastava operator, and we define here a similar transformation by means of an operator given by Ghanim and Darus, in U = { z : 0 < |z| < 1 }, and investigate a number of inclusion relationships of these classes. We also derive some interesting properties of these classes.